Nugumouinun genumugumouat igiu anishinabeg anumiajig [electronic resource] - Jones, Peter, 1802-1856 (Boston : Printed for the American Board of Commissioners for Foreign Missions by Crocker & Brewster, 1836)
Text in Ojibway. "Mitasui iniu gugikueuinun"--p. [45]-52. Electronic reproduction. Mode of access: Internet. 44